WELDING TECHNICAL CLINIC ANALYSIS OF WELDING SMAW WELDING IN VEHICLES OF DISTORTION RECESSING - Wibowo, Heri; Jatmiko, Riswan Dwi (Jurnal Penelitian Saintek, 2010)
Contplicated distortion alu,ays )tappens in metel melting and.freezirtg proL'ess on welding Lip trt now, the common merhod to recluce distnrtion are; base ntetal prehettling, heat irtput minirualization, welding process sequence, etc. the last has been u,setJ l:y tr'r,Uort, hov:ettet' lhe sequence ofbest effectivitlt and elficiency has not been yet studied. This research aims to l<now ffict of welding process sequence b), sttrdied 5 dil/brent v,elding route related to angle distortion (a), bending distortion (0), c'ross distortian (LI .l anci atial distortion (LP). 'tilelding process used sltielded metal arc welding, base metal ofST 37 and electrode of E6013; 2.6 mm and 3.2 mm of diameter. Fou'kinds oJ te,st used ungle gauge oJ 0.lo precision ctnd caliper of 0.05 mm precision.Based on the test, it could be known that the lov:est angle distortion toctk pluc:e on 3 tirues roule that was 3.07", while the highest happened at 5 times route methoci thai v'Lts 9.23". the lov'esl ben.ding distortion took place on I and 3 lintes route thal wctre 1.50 mm anci 1.52, respectit'e1.1:, wh.ile the highest happened at 5 times rrnrte ruethod that wqs 1 70 rnnt. Cross clistortictn ancl ctnglc distortion tended to have lowest distortion at 3 titnes route, v,hile axial distortion and bentling distortion at I and 3 times routes. All that kinds of dislortion had llte lowest valtte ctt 3 times rotfie v'hichwas the best welding route at sheet ntetal ctf 5 nmt thickness.